Suffering, sacrifice and servanthood in Israel - Ashby, G. W. (Old Testament essays, 2002)
Building on the redactional unity of Isaiah (i e, that Deutero-Isaiah based his message on that of Proto-Isaiah and that Trito-Isaiah followed suit) the following message was given to Israel : 'You are Yahweh's chosen people, chosen to bring justice, salvation and enlightenment to yourselves and to the world of nations. This is a calling, not to glory but to suffering, to hurt, to humiliation and to death as a sacrifice - and to victory, the victory of obedient servanthood. This message is for you, God's chosen and for your Messiah.' Through the sacrifice in suffering of Jesus, the Christ, this is still the message for Christians and for the Church. 'You are called to bring justice and salvation to the nations: this is a call to suffering, humiliation, death and victory.'